2018
DOI: 10.22159/ijpps.2018v10i2.23357
|View full text |Cite
|
Sign up to set email alerts
|

Betulin-3, 28-Diphosphate Salt Complexes With Amines and Their Antioxidant Activity

Abstract: Objective: Studies of composition, stability and antioxidant properties of the betulin-3, 28-diphosphate complexes with dopamine and trisamine. Methods:The betulin-3, 28-diphosphate (BDP) interaction with amines in a water-alcohol medium was studied by using spectral methods and potentiometric titration. Biochemical indexes such as catalase, superoxide dismutase (SOD), lactate dehydrogenase (LDH) activities and malondialdehyde (MDA) level were estimated in experiments on rats.Results: BDP was synthesized using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Betulin-3,28-diphosphate was synthesized according to the methods in [ 27 ]. Betulin (6.0 g, 13.56 mmol) was solved in the mixture of 120 mL of dioxane and 7.08 mL of pyridine (81.6 mmol) in a three-neck flask at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Betulin-3,28-diphosphate was synthesized according to the methods in [ 27 ]. Betulin (6.0 g, 13.56 mmol) was solved in the mixture of 120 mL of dioxane and 7.08 mL of pyridine (81.6 mmol) in a three-neck flask at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Quantum-chemical calculations were provided by HyperChem 8.0, Hypercube Inc, Gainesville, FL, USA (semiempirical method AM1). Size of the void between BDP molecules is 6 Å for dimer and 10 Å for tetramer [ 27 ].…”
Section: Figurementioning
confidence: 99%
“…As a result of this interaction, cavities are formed inside the dimeric or tetrameric structures, which can accommodate small molecules. Figure S6 shows dimeric or tetrameric structures formed by BDP [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, phytic acid forms different kinds of complexes with amines due to not only proton transfer, but also non-specific covalent binding [34]. Previously we showed that BDP like phytic acid forms salt complexes with amines [35] by proton transfer reaction like phosphoric acid.…”
Section: Fig 3: the Dependence Of Bdp Microspecies Distributions (%)mentioning
confidence: 99%
“…It is possible that such BDP ionization has the nature of the salt complex formation similar to BDP salt complexation with trisamine [35]. The composition of the BDP-trisamine complex was proved using Job's method, and the conditional stability constant equal to 1130 mol•l -1 was calculated [35]. The interaction of BDP with meglumine in a solution was also studied using 31 P-NMR spectra ( fig.…”
Section: The Acid-base Interaction Of Bdp With Megluminementioning
confidence: 99%